The Political-Security Dimension of the Free Papua Organization - Siregar, Hasrul Sani (Law Research Review Quarterly, 2016)
Indonesia's sovereignty over Papua has heated up a little, when the Free Papua Organization (OPM) opened its representative to open a campaign office in Oxford City, a state in the UK on April 28, 2013. The OPM move made diplomatic relations between Indonesia and Britain a little heated. In response to this, Indonesia has summoned the British Ambassador to Indonesia, Mark Canning, to confirm and clarify the issue. By Britain through its ambassador in Indonesia it has been clearly said that the UK fully supports Indonesian sovereignty over Papua and West Papua. The issue of opening the OPM office in Oxford City does not represent the Federal (central) government in London, explained Mark Canning further.